eCM 2012
DOI: 10.22203/ecm.v024a02
|View full text |Cite
|
Sign up to set email alerts
|

Sustained and promoter dependent bone morphogenetic protein expression by rat mesenchymal stem cells after BMP-2 transgene electrotransfer

Abstract: Document VersionPublisher's PDF, also known as Version of Record (includes final page, issue and volume numbers) Please check the document version of this publication:• A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…The BMP2 protein secretion from iPSC-MSCs and BMP2-iPSC-MSCs (passage 5 to 8) was evaluated by measuring BMP2 amount in the conditioned medium, as described previously [23]. Briefly, cells were cultured on 75 cm 2 TCPS flasks and the cell supernatants were collected during a 24-hour culture.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The BMP2 protein secretion from iPSC-MSCs and BMP2-iPSC-MSCs (passage 5 to 8) was evaluated by measuring BMP2 amount in the conditioned medium, as described previously [23]. Briefly, cells were cultured on 75 cm 2 TCPS flasks and the cell supernatants were collected during a 24-hour culture.…”
Section: Methodsmentioning
confidence: 99%
“…Gene therapy strategy has been used for this purpose because it has advantages over direct growth factor delivery, such as low cost and sustained long-term release [20]. Bone morphogenic protein 2 (BMP2), a member of the transforming growth factor β (TGFβ) superfamily, has a remarkable capability of inducing bone formation [2123]. Preclinical and clinical investigations have successfully applied BMP2 in the therapy of bone defects [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CMV promoter once was used as the standard promoter in most BMP transgene expression systems 40. However, Ferreira et al 41. have proved a fact that elongation factor-1α, (EF-1α), β-actin and GAPDH promoters are more efficient than the viral promoters such as CMV in driving gene expression, and provided the first in vitro evidence for a safe alternative to viral methods that permit efficient BMP-2 gene delivery and expression in MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Transgene electrotransfer is first highly efficient nonviral gene transfer method for most primary cells and for hard-to-transfect cell lines; it looks like a promising method. Ferreira et al 41. have compared a BMP-2 secretion rate of the control under CMV, eIF4A1, EF-1α, β-actin, GAPDH, fibronectin or osteocalcin promoters using electrotransfer into rat MSCs and showed that BMP-2 production correlated with sustained (up to 21 d) hBMP-2 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%